PEMODELAN FAILURE TIME PADA MAHASISWA BERHENTI STUDI DI UNIVERSITAS JEMBER - Hanifia, Fidiatma Foristy; Fatekurohman, M.; Anggraeni, Dian (Jurusan Matematika FMIPA Universitas Jember, 2020)
Problems in higher education concerning students are always interesting objects studied from any side. One of the problems faced by universities and students is stopping study. Stopping the study of students became a problem in universities, including the University of Jember. One of the statistical methods used is Survival Analysis. In its development, survival analysis was carried out by combining the concepts of Geometric regression. Geometric is one of the non linear regression for discrete data. Geometric regression modeling cannot be done with ordinary linear modeling, but must be done using the Generalized Linear Model (GLMs) method. In this study the variables used were gender, GPA, faculty, age of entry and entry point. The results of the study students stopped studying in the first semester 140 students. Average GPA of 1.54. 62.85% male sex. Student faculty of education and teacher stopped most studies. The student entry pathway stopped the most SBMPTBR studies and 54.40% were 18 years old. Significant influential factors for stopping the study were GPA, gender and entry point. From the Geometric opportunity, it was found that female students were slower when they stopped studying than men. The faculty stops studying at the latest is the Faculty of Medicine. Keywords: Drop Out, Failure Time, Regrition Geometric Method